Numerical approximation of the integral generalized k-fractional Hilfer type - Rodríguez-Giraldo, Ronald Gentil; Paredes, Jorge Morales; Plata, Adrián Ricardo Gómez; Costa, Felix Silva (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
Recent studies show the importance of the fractional calculation in the modeling of problems in physics and engineering among others. These dynamic systems generally need numerical approximations to estimates of your solutions. This work presents an approximation numerical for k-fractional integral using as techniques of approximation the rule of the rectangle and the rule of the trapezoid.
Keywords: k-fractional integral; rule of the rectangle; rule of the trapezoid.